13. Check list in intraoperative neurophysiologic monitoring. Issue 12 (December 2017) - Motti, L.; Torre, G.; Basile, C.; Barsotti, M.; Ferrari, F.
Abstract : The evidence that the failures in communication, such as omission of information, wrong interpretations, conflicts in the team members, are frequent cause of medical malpractice and adverse events, is stronger. It constitutes a relevant obstacle to the safety and quality of the health care. The creation of 5 checklist model, according to the type of monitoring (supratentorial, subtentorial, cervico-dorsal, lombosacral cauda and peripherical), brought us to implement the communication among the surgery room's team, as instrumentalist, surgery nurse, anesthetist, neurosurgeon and to reduce the risk of malpractice. The checklist is divided in three phases, as follows: Sign in - before the surgery, record of the personnel presents: communication with instrumentalist, anesthetist and surgery team about the different medical coverages and safe patient handling and mobility. Time out – during the IOMN recording: communication of possible changes of signal and possible remedies. Sign out – at the end of the IOMN recording: communication of possible adverse events, material removal, saving of biological data/video and reporting. The checklist has been experimentally used in our Hospital for 24 months, with subsequent validation done by Hospital itself.